TEKNOLOGI BUDIDAYA KEDELAI DENGAN PENDEKATAN PENGELOLAAN TANAMAN TERPADU (PTT) DI KAB KULON PROGO D.I. YOGYAKARTA - Suradal, Suradal; Bekti, Utomo Bimo; Anshori, Arif (Caraka Tani: Journal of Sustainable Agriculture, 2017)
Kulon Progo Regency is one producer of soybeans in D.I. Yogyakarta. The research aims to find out the result of soybean and farmers perception on soybean production technologies with an approach of integrated crop management (ICM) in Kulon Progo. The research was conducted in April-November 2013. 10 soybean varieties were planted to determine the level of productivity. Pattern and timing of planting explored through interviews with farmers and field inspections. Interviews were conducted with farmers to determine the perceptions of soybean production technology with the approach of integrated crop management (ICM) and in particular soybean varieties. The data were analyzed descriptively. The results showed in Kulon Progo Regency soybeans planted in irrigated land, rainfed lowland and upland, adjust the availability of water. The results showed in Kulon Progo Regency soybeans planted in irrigated land, rainfed lowland and upland, adjust the availability of water. Soybean production technology is not implemented by farmers as a whole, depends on the conditions of agro-ecosystems and agricultural inputs. In general, farmers agree with soybean production technology components with the approach of integrated crop management (ICM). Some farmers do not agree with the manufacture of drainage, mulching straw and harvest when 95% of the leaves have yellowed. Varieties Detam-2, Ijen and Tanggamus more adaptive and give higher yields. However, soybean farmers in Kulon Progo Regency prefer largely seeded soybean as Argomulyo and Burangrang. Gema varieties favored for short-lived.